2019
DOI: 10.1152/ajpregu.00254.2018
|View full text |Cite
|
Sign up to set email alerts
|

The highly efficient powerhouse in the Wistar audiogenic rat, an epileptic rat strain

Abstract: The Wistar audiogenic rat (WAR) is an animal model of tonic-clonic epileptic seizures, developed after genetic selection by sister × brother inbreeding of Wistar rats susceptible to sound stimuli. Although metabolic changes have been described in this strain, nothing is known about its mitochondrial metabolism. Here, we addressed mitochondrial aspects of oxidative phosphorylation, oxidative stress, biogenesis, and dynamics in liver, skeletal muscle, and heart of male WARs and correlating them with physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…In a previous study of our group, we found the same mitochondrial and oxidative profile in the liver, soleus muscle and cardiac tissue of WAR (60). In these organs, the changes were associated with higher expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α) and mammalian target of rapamycin (mTOR).…”
Section: Discussionsupporting
confidence: 73%
“…In a previous study of our group, we found the same mitochondrial and oxidative profile in the liver, soleus muscle and cardiac tissue of WAR (60). In these organs, the changes were associated with higher expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α) and mammalian target of rapamycin (mTOR).…”
Section: Discussionsupporting
confidence: 73%
“…Epilepsy is a heterogeneous brain disorder affecting 1 to 3% of the population worldwide. The main symptom of epilepsy is the onset of spontaneous seizures resulting from an impaired excitatory/inhibitory balance [ 1 ]. Temporal lobe epilepsy (TLE) is the most frequent type of epilepsy, and the most refractory type to drug treatment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since clinical studies cannot provide sufficient information about the precise mechanisms underlying seizure susceptibility and epileptogenesis, animal models for epilepsy are a reliable approach for such mechanistic studies [ 1 ]. Pilocarpine (Pilo) is one of the most widely used convulsant agents that induce status epilepticus (SE), followed by neurochemical alterations and structural and functional changes similar to those observed in epileptic patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%